2010
DOI: 10.1111/j.1749-7345.2010.00380.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapy of Aeromonas hydrophila-infected Goldfish, Carassius auratus

Abstract: Etiological investigations have often implicated Aeromonas hydrophila, a heterotrophic Gram‐negative pathogenic aquatic bacterium, in a variety of systemic and localized fish diseases. The aim of this study was to test the efficacy of a herbal concoction against A. hydrophila‐infected goldfish (Carassius auratus). After the pathogen was intramuscularly injected, scales sloughed off on the site of administration, with the appearance of a muscular hemorrhagic protuberance that progressed into an extensive ulcera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…In similar studies using other herbs, Abdel‐Tawwab et al () and Abdel‐Tawwab () found that supplementing diets with green tea and American ginseng enhanced the resistance of Nile tilapia against A. hydrophila infection. Harikrishnan et al () treated A. hydrophila ‐infected goldfish, Carassius auratus , with aqueous herbal concoction obtained from three medicinal plants (neem, tulsi, and turmeric), and examined the histopathologic and recovery changes in lateral muscle, gills, liver, and heart tissues. They found that the dip treatment with the concoction (1% herbal concoction dip treatment for 5 min/d daily at 1100 h) restored the histoarchitecture of the altered fish tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In similar studies using other herbs, Abdel‐Tawwab et al () and Abdel‐Tawwab () found that supplementing diets with green tea and American ginseng enhanced the resistance of Nile tilapia against A. hydrophila infection. Harikrishnan et al () treated A. hydrophila ‐infected goldfish, Carassius auratus , with aqueous herbal concoction obtained from three medicinal plants (neem, tulsi, and turmeric), and examined the histopathologic and recovery changes in lateral muscle, gills, liver, and heart tissues. They found that the dip treatment with the concoction (1% herbal concoction dip treatment for 5 min/d daily at 1100 h) restored the histoarchitecture of the altered fish tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of plant extracts to fish by immersion (Table ) has been tested in the treatment of diseases as alternative to traditional drugs and the protocols adopted included single or repeated treatments (Harikrishnan, Rani & Balasundaram ; Harikrishnan, Balasundaram & Bhuvaneswari ; Harikrishnan & Balasundaram ; Rajendiran, Natarjan & Subramanian ; Harikrishnan, Balasundaram, Moon, Kim, Kim & Heo ; Harikrishnan, Moon, Kim, Kim & Heo ; Rattanachaikunsopon & Phumkhachorn ). Dip treatment is logistically more practical for a large number of small fish (weighing less than 5 g) but dilution, exposure time and levels of efficacy are usually not well defined for the majority of immunostimulants (Sakai ; Galindo‐Villegas & Hosokawa ).…”
Section: Route Of Plant Administration and Dosagementioning
confidence: 99%
“…A. hydrophila (MTCC 646) was obtained from the Institute of Microbial Technology, Government of India, Chandigarh, and maintained in the laboratory under standard conditions (Harikrishnan et al 2003). The identity of A. hydrophila was verified using biochemical tests, as described previously (Harikrishnan et al 2010). Subcultures were maintained on tryptic soy agar (TSA; Himedia) on slopes at 5°C and routinely tested for pathogenesis (Joseph & Carnahan 1994) by inoculation into American eels (Le Sueur) (Davis & Hayasaka 1983).…”
Section: Methodsmentioning
confidence: 99%
“…One promising method of controlling infection in aquaculture is strengthening the defence mechanisms of fish through prophylactic administration of probiotics and herbs (Gibson et al 1997, Harikrishnan et al 2003, 2010, Sharifuzzaman & Austin 2009). Probiotics such as lactic acid bacteria, produce specific compounds such as bacteriocins or bacteriostatic peptides (Klaenhammer 1988) that inhibit the growth of fish pathogens, including Aeromonas hydrophila, Vibrio anguillarum and A. salmonicida (Lewus et al 1991, Gildberg et al 1995, Santos et al 1996, in addition to improving water quality (Skjermo & Vadstein 1999).…”
Section: Introductionmentioning
confidence: 99%